THE RESPONSIBILITY OF THE INTERNAL AUDITOR FOR PROCEDURES. - Campbell, L. E. (The Accounting Review, 1955)
This article focuses on the responsibility of the internal auditor for procedures. Internal Auditing is the independent appraisal activity within an organization for the review of the accounting, financial, and other operations as a basis for protective and constructive service to management. It is a type of control which functions by measuring and evaluating the effectiveness of other types of control. It deals primarily with accounting and financial matters, but it may also properly deal with matters of an operating nature. The article also says that Internal Auditing should not include responsibilities for procedures which are essentially a part of the regular operations of a complete and adequate system or of a properly organized operating department. If the internal auditor is to do a satisfactory job in the matter of auditing procedures, he is presumed to know as much about the design and installation of procedures as do the systems and procedures experts. This calls for proper relations with the latter.